Enhancing Selective Attention in Children with Learning Disorders: Efficacy of Executive Functions Training - Bulut, Solmaz; Bukhori, Baidi; Parsakia, Kamdin (KMAN Counseling & Psychology Nexus, 2024)
The study aimed to evaluate the effectiveness of an executive functions training program in improving selective attention among children with specific learning disorders. It sought to assess the immediate and sustained impacts of the intervention by comparing changes in selective attention scores between experimental and control groups across pre-test, post-test, and follow-up measurements. A total of 40 children diagnosed with specific learning disorders were recruited and randomly assigned to either the experimental (n=20) or control (n=20) groups. The experimental group underwent a comprehensive executive functions training program, while the control group received no intervention. Selective attention was assessed for all participants at three time points: pre-test, immediately post-intervention (post-test), and at a follow-up session. Descriptive statistics, mixed-model Analysis of Variance (ANOVA), and Bonferroni post-hoc tests were employed to analyze the data. The experimental group demonstrated significant improvements in selective attention scores from pre-test to post-test (mean difference = 6.40, p = 0.001) and maintained these improvements at follow-up (mean difference = 6.55, p = 0.001). In contrast, the control group showed minimal changes across the same periods. Statistical analyses confirmed significant effects of time, group, and time × group interaction on selective attention scores, with large effect sizes (Eta² > 0.37) indicating the substantial impact of the intervention. The executive functions training program was highly effective in enhancing selective attention among children with specific learning disorders. The intervention led to significant and sustained improvements, highlighting the potential of targeted cognitive training in supporting children with learning challenges. These findings suggest that incorporating executive functions training into therapeutic and educational strategies for children with learning disorders could substantially benefit their cognitive development and academic performance.